Copper magnetic centers in oxygen deficien (R=Nd, Sm): An EPR and magnetic study - V. Likodimos; Guskos, N.; Gamari-Seale, H.; Koufoudakis, A. (Physical Review B - Condensed Matter and Materials Physics, 1996)
EPR and magnetic results are reported for oxygen deficient, nonsuperconducting R(Formula presented)(Formula presented)(Formula presented) (R=Nd, Sm) compounds. The magnetic-susceptibility χ(T) and isothermal M(H) data are analyzed as the superposition of the rare-earth (Formula presented) contribution with another strongly ferromagnetic (FM) contribution arising from FM copper clusters with large total spin S. The rare-earth paramagnetic contribution in χ(T) and M(H) are calculated using the results of consistent crystal-field analysis (intermediate coupling wave functions, J-mixing effects) of (Formula presented) and (Formula presented) ions. The corresponding EPR spectra comprise an intense, almost isotropic EPR line whose intensity I(T) exhibits a ferromagnetic behavior, while (Formula presented) and the linewidth Δ(Formula presented) diverge at T<10 K indicating the presence of slowly fluctuating “internal” fields. The origin of the FM clusters is related to spin-polarized copper clusters through oxygen holes in the Cu(1) or Cu(2) layers, while the ferromagnetic interaction of the (Formula presented)(1) with the (Formula presented)(2) moments may be involved in the low-temperature (T<10 K) behavior of the EPR parameters. On increasing the oxygen deficiency, the ferromagnetic contribution is drastically reduced and more isolated (Formula presented) centers appear as shown by the corresponding EPR data. Exact simulation of the latter anisotropic EPR spectra, shows that the anisotropic linewidths Δ(Formula presented) (i=x, y, z) gradually broaden at low temperatures, while the intensity I(T) shows antiferromagnetic behavior. EPR measurements on an “aged” (Formula presented)(Formula presented)(Formula presented)(Formula presented)(Formula presented) sample revealed that the (Formula presented) EPR spectrum intensifies with time, a behavior probably related to oxygen ordering processes or to surface degradation effects. Analysis of the EPR resonance of (Formula presented) and (Formula presented) ions in combination with the absence of the corresponding EPR spectra indicate the presence of very fast spin-lattice relaxation of the rare-earth ions. © 1996 The American Physical Society.